ENTREPRENEURSHIP DALAM PELAYANAN GEREJAWI: ANALISA PERAN ENTREPRENEURSHIP BAGI PELAYANAN GEREJAWI BERDASARKAN KISAH PARA RASUL - Sandiki, Reza; Kustiadi, Josse (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2024)
Entrepreneurship is considered a key component in global economic development, playing a central role in shaping and driving economic dynamics. Entrepreneurs strengthen global economic growth by creating business opportunities, developing innovations, and generating employment, both in formal and informal business sectors. The engagement of entrepreneurs in facing global challenges demonstrates their adaptability and ability to explore and capitalize on new opportunities. Entrepreneurship development not only affects economic aspects but also significantly impacts the church and the Christian world. The concept of Christian Entrepreneurship, associated with the teachings of Apostle Paul, presents new opportunities and challenges for the church. Paul is regarded as a pioneer who introduced the concept of Pastorpreneur, integrating spiritual activities with an entrepreneurial attitude in spreading the Gospel and building Christian communities. This research utilizes a qualitative descriptive method through literature review to explore the entrepreneurship concept in the Acts of the Apostles. The findings show that entrepreneurship principles have a significant impact on shaping the character and approach of missionaries and Christian ministers. They are inspired by the entrepreneurial spirit to be adaptive and responsive to changes, creating a foundation for relevant and effective ministry.